Adaptation and validation studies of the Brief Differentiation of Self Inventory-Revised (Brief DSI-R) in heterosexual and sexual minority Portuguese young adults - Borges, Flavia Vanessa Rocha (2021)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação